Azulene hydrazide-hydrazones for selective targeting of pancreatic cancer cells - Brogyányi, Tereza; Kaplánek, Robert; Kejík, Zdeněk; Hosnedlová, Božena; Antonyová, Veronika; Abramenko, Nikita; Veselá, Kateřina; Martásek, Pavel; Vokurka, Martin; Richardson, Des R; Jakubek, Milan (Biomedicine & pharmacotherapy, 2022)
Dysregulation of iron homeostasis is one of the important processes in the development of many oncological diseases, such as pancreatic cancer. Targeting it with specific agents, such as an iron chelator, are promising therapeutic methods. In this study, we tested the cytotoxicity of novel azulene hydrazide-hydrazone-based chelators against pancreatic cancer cell lines (MIA PaCa-2, PANC-1, AsPC-1). All prepared chelators (compounds 4-6) showed strong cytotoxicity against pancreatic cancer cell lines and high selectivity for cancer cell lines compared to the healthy line. Their cytotoxicity is lower than thiosemicarbazone-based chelators Dp44mT and DpC, but significantly higher than hydroxamic acid-based chelator DFO. The chelator tested showed mitochondrial and lysosomal co-localization and its mechanism of action was based on the induction of hypoxia-inducible factor-1-alpha (HIF-1α), N-myc downstream-regulated gene-1 (NDRG1) and transferrin receptor 1 (TfR1). This strongly implies that the cytotoxic effect of tested chelators could be associated with mitophagy induction. Lipinski's rule of five analyses was performed to determine whether the prepared compounds had properties ensuring their bioavailability. In addition, the drug-likeness and drug-score were calculated and discussed.
Keywords: thiosemikarbazony; chelátory železa; azuleny; nádorové buněčné linie; Hydrazone; Receptors, Transferrin; HIF-1α; Chelators; nádory slinivky břišní; železo; Cell Line, Tumor; Hydrazones; Iron Chelating Agents; hydrazony; Iron; NDRG1; Humans; receptory transferinu; Cancer; Pancreatic Neoplasms; kyseliny hydroxamové; Hydrazines; Thiosemicarbazones; hydraziny; TfR1; Azulenes; lidé; Hydroxamic Acids